Acute renal failure following Yersinia pseudotuberculosis septicaemia. Issue 743 (September 1987) - Davenport, A.; O'Connor, B.; Finn, R.
Abstract : Although Yersinia pseudotuberculosis has not been previously reported to cause acute renal failure, it accounted for two cases reported here out of eighty referrals with acute renal failure to our renal unit over the last year. This may suggest that the incidence of Yersinia pseudotuberculosis may be greater than that previously reported, and it should be suspected in patients presenting with bloody diarrhoea in association with renal failure. The septicaemic form of the disease is life threatening and requires intensive supportive therapy.